2022
DOI: 10.1039/d2cp02619h
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized nona-silicide [Si9R3] Zintl clusters: a new class of superhalogens

Abstract: Superatoms, due to their various applications in redox and materials chemistry, have been a major topic of study in cluster science. Superhalogens constitute a special class of superatoms that mimic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…The VDE is determined by taking the difference between the energies of the anion and the corresponding neutral species possessing the anion geometry, as shown in equation 1. [4,57,60]…”
Section: Dft Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The VDE is determined by taking the difference between the energies of the anion and the corresponding neutral species possessing the anion geometry, as shown in equation 1. [4,57,60]…”
Section: Dft Calculationsmentioning
confidence: 99%
“…The electron-withdrawing groups pull the electron density of the clusters toward themselves, and hence, the propensity of clusters to accept electrons increases, which amplifies the VDE values. [60] In contrast, the electron-donating group (À CH 3 ) decreases the VDE values slightly. For most anions, it can be noted that À NCS and À CF 3 increase the VDE values to the maximum extent, indicating greater stability of the clusters with these substituents.…”
Section: Vertical Detachment Energy (Vde)mentioning
confidence: 99%
“…cluster can be explained using the Wade-Mingos and Jellium electronic shell closure rules, respectively. [26,64] It possesses a Nido structure (follow 4n + 4 rule, where n is the number of vertices in the cluster, here n = 9 and valence electrons of Si = 4) and contains a stable 40 (9x4 + 4) magic number of electrons. The electronic configuration of Si 9…”
Section: àmentioning
confidence: 99%
“…[23][24][25] Zintl cluster is polyatomic versatile multianion species belong to a main group compound that exhibits unique reactivity and can participate in diverse chemical transformations. [26][27][28][29][30][31][32] Recently, various studies shown that the nonagermanium based Zintl cluster (Ge 9 ) can be act as a nucleophile due to its presence of external lone pairs. [25,[32][33][34][35] Therefore, one promising avenue is using Zintl clusters as potential cleaving agent for disulfide bonds.…”
Section: Introductionmentioning
confidence: 99%
“…They can be utilized to create uncommon CT salts whose counterparts have a low electron affinity (EA). In silico design and characterization of superalkalis based on Zintl ions and the superatom compounds with an NLO response have been reported by some research groups along with Zintl clusters as a new class of superhalogens which can be seen in the literature ( Reddy et al, 2018b , Reddy et al, 2018a ; Sun et al, 2018 ; Sinha et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%